Biomass and potassium chlorate solid-state two-phase energetic material and preparation method thereof
Patent Information
- Application Number
- CN202611252733.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明的目的在于克服现有技术中的不足,提供一种生物质与氯酸钾固态二相含能材料及其制备方法,解决“现有生物质和氯酸钾含能材料难以同时兼顾安全性能、储存稳定性与能量释放效率”的技术问题
(1)本发明通过生物质基材的化学改性、氯酸钾的木质素磺酸钠微胶囊包覆以及纳米二氧化铈与硬脂酸锌复配的三种技术手段的协同作用,构建了兼顾安全性能、储存稳定性与燃烧性能的固态二相含能材料体系。克服了传统含能材料安全性与能量释放效率难以兼顾的技术矛盾。
Smart Images

Figure CN122977907A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energetic materials technology, specifically to an energetic material consisting of biomass and potassium chlorate in a solid two-phase state and its preparation method. Background Technology
[0002] Energetic materials are essential foundational materials for the national economy and defense industry. In the civilian sector, scenarios such as industrial blasting, engineering pyrotechnics, and emergency energy generators all rely on safe and efficient energy supply. With increasing global emphasis on sustainable development, developing widely available and renewable biomass-based energetic materials has become a crucial direction. Biomass resources (such as straw and wood flour) have advantages such as carbon neutrality, high oxygen content, and abundant sources, making them a suitable fuel alternative to traditional non-renewable fossil resources, aligning with the demands of green and low-carbon development. Potassium chlorate, as a classic oxidant, is widely used in civilian pyrotechnics and signal flares due to its high oxygen content (theoretically up to 39.2%), moderate decomposition temperature, and low cost. Therefore, theoretically, combining biomass with potassium chlorate could construct an energetic material system that combines environmental friendliness with cost advantages.
[0003] However, this technological approach faces a series of technical bottlenecks that are difficult to overcome in existing technologies, making it difficult to achieve effective industrial application. First, the surface of biomass substrates is rich in functional groups such as polar hydroxyl groups, exhibiting strong polarity and hydrophilicity. Potassium chlorate, as an inorganic salt, shows significant incompatibility between the two in terms of physical and chemical properties. This results in poor interfacial bonding between the fuel phase and the oxidant phase during conventional mechanical mixing, easily leading to uneven micro-distribution. Ultimately, this causes incomplete combustion reaction, large fluctuations in energy release, and the generation of large amounts of toxic and harmful gases such as carbon monoxide, reducing energy utilization efficiency.
[0004] Secondly, safety is a key obstacle limiting the application of this system. Potassium chlorate itself is highly hygroscopic, easily absorbing moisture from the environment during storage and causing deliquescence and clumping. This not only leads to the deterioration of material properties but also significantly increases its mechanical sensitivity during subsequent processing, transportation, and use, increasing the risk of accidental combustion or explosion. Although existing technologies attempt to improve safety by adding inert passivating agents or physical coatings, these methods often come at the cost of energy density and combustion rate, making it difficult to achieve a good balance between safety and performance.
[0005] Furthermore, the reaction kinetics of existing biomass-potassium chlorate systems are difficult to precisely control. Due to the lack of effective catalytic and stabilizing mechanisms, the combustion rate of these materials is often low or unstable, making it difficult to meet the high power output requirements of specific applications such as rapid emergency energy startup. At the same time, the over-reliance on inert additives to ensure safety further exacerbates the deterioration of energy release efficiency, making it impossible for this system to match the overall performance of traditional energetic materials.
[0006] Therefore, how to fully utilize the respective advantages of biomass and potassium chlorate, and simultaneously solve the technical problems of poor interfacial compatibility, insufficient long-term storage stability, and the mutual constraints between safety performance and energy release efficiency through a systematic technical solution, and achieve a significant improvement in the overall performance of the materials, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide a biomass and potassium chlorate solid two-phase energetic material and its preparation method, thereby solving the technical problem that "existing biomass and potassium chlorate energetic materials are difficult to simultaneously achieve safety performance, storage stability and energy release efficiency".
[0008] To achieve the above objectives, the present invention is implemented using the following technical solution: In a first aspect, the present invention provides a biomass and potassium chlorate solid two-phase energetic material, wherein the energetic material is formed by compounding a fuel phase and an oxidant phase and pressing them together. The fuel phase comprises a biomass substrate, a modifier, a binder, and functional additives. The biomass substrate is chemically modified by the modifier and then mixed with the binder and the functional additives to form fuel phase particles. The adhesive is polyvinyl alcohol; The oxidant phase is potassium chlorate microcapsules with a core-shell structure formed by encapsulation with sodium lignosulfonate. The functional additive is composed of nano-cerium dioxide and zinc stearate.
[0009] Preferably, the biomass substrate is selected from one of poplar wood powder, bamboo powder, and corn stalk powder.
[0010] Preferably, the modifier is selected from citric acid and maleic anhydride.
[0011] Secondly, this invention provides a method for preparing a solid-state two-phase energetic material composed of biomass and potassium chlorate, comprising the following steps: (1) Dissolve sodium lignosulfonate in deionized water to prepare a coating solution, add potassium chlorate powder and stir evenly to prepare a suspension, spray dry, collect and sieve to obtain potassium chlorate microcapsules coated with sodium lignosulfonate. (2) After drying the biomass substrate, mix it with the modifier, add deionized water and stir to react. After the reaction is completed, filter and dry to obtain the modified biomass substrate. (3) The modified biomass substrate is mixed with binder, nano-cerium dioxide and zinc stearate, and deionized water is added to adjust the moisture content before extrusion granulation to obtain fuel phase particles; (4) The fuel phase particles and the potassium chlorate microcapsules are mixed evenly and then pressed into shape to obtain an energetic material.
[0012] Specifically, the fuel phase particles in step (3) include, by weight, 80-90 parts of modified biomass substrate, 5-7 parts of binder, 2-4 parts of nano-cerium dioxide and 1.5-4.5 parts of zinc stearate.
[0013] Specifically, the modified biomass substrate mentioned in step (2) comprises, by weight, 75 to 88 parts of dried biomass substrate and 4 to 8 parts of modifier.
[0014] Specifically, the parameters for spray drying in step (1) are: inlet air temperature of 180~200℃, outlet air temperature of 80~90℃, and feed rate of 5~10mL / min.
[0015] Specifically, in step (4), the fuel phase particles account for 20-28% of the total mass of the energetic material, and the potassium chlorate microcapsules account for 72-80% of the total mass of the energetic material.
[0016] Specifically, the pressing pressure in step (4) is 15~20MPa, the pressing temperature is 60~70℃, and the pressing time is 20~40s.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) This invention constructs a solid two-phase energetic material system that balances safety, storage stability and combustion performance through the synergistic effect of three technical means: chemical modification of biomass substrate, microcapsule coating of potassium chlorate with sodium lignosulfonate, and compounding of nano-cerium dioxide and zinc stearate. This overcomes the technical contradiction of traditional energetic materials that are difficult to balance safety and energy release efficiency.
[0018] (2) The present invention uses a modifier to chemically modify the biomass substrate, which can gently modify the hydroxyl groups on the biomass surface, reduce its polarity, improve the interfacial compatibility with potassium chlorate oxidant, and reduce the active sites at the cellulose molecular level, thereby significantly reducing the impact sensitivity and friction sensitivity of the material; combined with the dense core-shell coating structure formed by sodium lignosulfonate on the surface of potassium chlorate, it can effectively isolate the intrusion of environmental moisture, inhibit the moisture absorption, clumping and decomposition failure of potassium chlorate during long-term storage, so that the material can still maintain stable energy output performance in high temperature and high humidity environments.
[0019] (3) This invention introduces a novel functional additive, a mixture of nano-cerium dioxide and zinc stearate in a specific ratio, into the fuel phase. Nano-cerium dioxide provides catalytically active sites, promoting electron transfer between the fuel and oxidant phases and accelerating the combustion kinetics. Zinc stearate forms a lubricating protective layer on the particle surface, reducing the probability of frictional heat generation between particles and simultaneously improving the hydrophobic properties of the system. The synergistic effect of these two additives can increase the combustion rate while reducing the generation of toxic and harmful gases such as carbon monoxide, achieving a balance between energy release efficiency and environmental friendliness. Attached Figure Description
[0020] Figure 1 This is a comparison chart of the combustion rates of energetic materials in Example 1 and Comparative Examples 1-3 of the present invention.
[0021] Figure 2 The performance degradation curves of energetic materials in Example 1 and Comparative Examples 1-3 of this invention after 12 months of storage are shown. Detailed Implementation
[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0023] To address the shortcomings of biomass-potassium chlorate energetic material systems: the large polarity difference between the fuel phase and the oxidant phase, resulting in weak interfacial bonding between the two phases; the high hygroscopicity of potassium chlorate, which easily deliquesces and leads to a decline in storage performance; and the difficulty in simultaneously achieving low mechanical sensitivity and high combustion rate, existing single modification methods cannot solve the above problems at the same time.
[0024] Therefore, this invention employs a synergistic design from three aspects: two-phase interface regulation, oxidant coating for moisture protection, and enhanced combustion kinetics, to provide a method for preparing a solid two-phase energetic material composed of biomass and potassium chlorate. The specific steps are as follows: (1) Potassium chlorate microcapsule coating: By weight, 15-17 parts of sodium lignosulfonate were added to deionized water to prepare a coating aqueous solution with a mass fraction of 15%; then 70-80 parts of potassium chlorate powder were added and stirred evenly to prepare a suspension; the suspension was sent to a spray dryer with an inlet air temperature of 180-200℃, an outlet air temperature of 80-90℃, and a feed rate of 5-10 mL / min. After atomization, drying, and solidification into a film, the film was collected and sieved to obtain potassium chlorate microcapsules. (2) Pretreatment of biomass substrate: Place the biomass substrate in a forced-air drying oven and dry it at 90~100℃ for 4~5h; take 75~88 parts of dried poplar wood powder and mix it with 4~8 parts of citric acid by weight, add deionized water to the solid-liquid ratio of 1:2~4, stir and react at 200r / min at 60~70℃ for 2~3h, after the reaction is completed, vacuum filter, and dry the filter cake at 80℃ to constant weight to obtain modified wood powder; (3) Preparation of fuel phase: By weight, 80-90 parts of modified wood flour, 5-7 parts of polyvinyl alcohol, 2-4 parts of nano-cerium dioxide and 1.5-4.5 parts of zinc stearate are mixed, and deionized water is added to adjust the moisture content to 15-20%. The mixture is extruded and granulated using a twin-screw extruder at 80-90℃ and a screw speed of 100-130r / min, and then cut into fuel phase particles with a particle size of 2mm. (4) Two-phase mixing and molding: By weight, 20-28 parts of fuel phase particles and 72-80 parts of potassium chlorate microcapsules are added to a three-dimensional mixer and mixed at 30-40 r / min for 15-20 min. The coefficient of variation of the mixing uniformity is ≤5%. The mixture is loaded into a mold and pressed at 15-20 MPa and 60-70℃ for 20-40 s to obtain the finished energetic material.
[0025] In the above preparation method, the biomass substrate has a particle size of 180 mesh, a cellulose content ≥48%, and a moisture content ≤6%; the potassium chlorate powder has a particle size of 50-100 mesh, a purity ≥99.5%, a chloride ion content ≤0.08%, and a moisture content ≤0.4%. The sodium lignosulfonate is industrial grade, and the citric acid is analytical grade with a purity ≥99.5%. The polyvinyl alcohol has a molecular weight of 1800. The nano-cerium dioxide has a particle size of 20 nm, and the zinc stearate is industrial grade. The deionized water has a conductivity ≤5 μS / cm. In the compression molding step, the molding density is 1.3-1.5 g / cm³.
[0026] Example 1; (1) Potassium chlorate microcapsule coating: By weight, 15 parts of sodium lignosulfonate were added to deionized water to prepare a coating aqueous solution with a mass fraction of 15%; then 70 parts of potassium chlorate powder were added and stirred evenly to prepare a suspension; the suspension was sent to a spray dryer with an inlet air temperature of 180℃, an outlet air temperature of 80℃, and a feed rate of 5mL / min. After atomization, drying, and solidification into a film, the film was collected and sieved to obtain potassium chlorate microcapsules. (2) Biomass substrate pretreatment: Poplar wood powder was placed in a forced-air drying oven and dried at 90°C for 4 hours; 75 parts of dried poplar wood powder were mixed with 4 parts of citric acid by weight, and deionized water was added to make the solid-liquid ratio 1:2. The mixture was stirred at 200 r / min at 60°C for 2 hours. After the reaction was completed, the mixture was vacuum filtered and the filter cake was dried at 80°C to constant weight to obtain modified wood powder. (3) Preparation of fuel phase: By weight, 80 parts of modified wood flour, 5 parts of polyvinyl alcohol, 2 parts of nano cerium dioxide and 1.5 parts of zinc stearate are mixed, deionized water is added to adjust the moisture content to 15%, and the mixture is extruded and granulated at 80°C and 100 r / min using a twin-screw extruder, and then cut into fuel phase particles with a particle size of 2 mm. (4) Two-phase mixing and molding: By weight, 20 parts of fuel phase particles and 80 parts of potassium chlorate microcapsules are added to a three-dimensional mixer and mixed at 30 r / min for 15 min. The coefficient of variation of the mixing uniformity is ≤5%. The mixture is loaded into a mold and pressed at 15 MPa and 60℃ for 20 s to obtain the finished energetic material.
[0027] Example 2; (1) Potassium chlorate microcapsule coating: By weight, 16 parts of sodium lignosulfonate were added to deionized water to prepare a coating aqueous solution with a mass fraction of 15%; then 75 parts of potassium chlorate powder were added and stirred evenly to prepare a suspension; the suspension was sent to a spray dryer with an inlet air temperature of 190℃, an outlet air temperature of 85℃ and a feed rate of 8mL / min. After atomization, drying and solidification into a film, the film was collected and sieved to obtain potassium chlorate microcapsules. (2) Biomass substrate pretreatment: Poplar wood powder was placed in a forced-air drying oven and dried at 95℃ for 4.5h; 82 parts by weight of dried poplar wood powder were mixed with 6 parts by weight of citric acid, and deionized water was added to a solid-liquid ratio of 1:3. The mixture was stirred at 200r / min at 65℃ for 2.5h. After the reaction was completed, the mixture was vacuum filtered, and the filter cake was dried at 80℃ to constant weight to obtain modified wood powder. (3) Preparation of fuel phase: By weight, 85 parts of modified wood flour, 6 parts of polyvinyl alcohol, 3 parts of nano cerium dioxide and 3.5 parts of zinc stearate were mixed, and deionized water was added to adjust the moisture content to 18%. The mixture was extruded and granulated at 85°C and 120 r / min using a twin-screw extruder, and then cut into fuel phase particles with a particle size of 2 mm. (4) Two-phase mixing and molding: By weight, 25 parts of fuel phase particles and 75 parts of potassium chlorate microcapsules are added to a three-dimensional mixer and mixed at 35 r / min for 18 min. The coefficient of variation of the mixing uniformity is ≤5%. The mixture is loaded into a mold and pressed at 18 MPa and 65℃ for 30 s to obtain the finished energetic material.
[0028] Example 3; (1) Potassium chlorate microcapsule coating: By weight, 17 parts of sodium lignosulfonate were added to deionized water to prepare a coating aqueous solution with a mass fraction of 15%; then 80 parts of potassium chlorate powder were added and stirred evenly to prepare a suspension; the suspension was sent to a spray dryer with an inlet air temperature of 200℃, an outlet air temperature of 90℃ and a feed rate of 10mL / min. After atomization, drying and solidification into a film, the film was collected and sieved to obtain potassium chlorate microcapsules. (2) Biomass substrate pretreatment: Poplar wood powder was placed in a forced-air drying oven and dried at 100℃ for 5h; by weight, 88 parts of dried poplar wood powder were mixed with 8 parts of citric acid, and deionized water was added to a solid-liquid ratio of 1:4. The mixture was stirred at 200r / min at 70℃ for 3h. After the reaction was completed, the mixture was vacuum filtered, and the filter cake was dried at 80℃ to constant weight to obtain modified wood powder. (3) Preparation of fuel phase: 90 parts by weight of modified wood flour, 7 parts of polyvinyl alcohol, 4 parts of nano cerium dioxide and 4.5 parts of zinc stearate are mixed, deionized water is added to adjust the moisture content to 20%, and the mixture is extruded and granulated at 90°C and 130 r / min using a twin-screw extruder, and then cut into fuel phase particles with a particle size of 2 mm. (4) Two-phase mixing and molding: By weight, 28 parts of fuel phase particles and 72 parts of potassium chlorate microcapsules were added to a three-dimensional mixer and mixed at 40 r / min for 20 min. The coefficient of variation of the mixing uniformity was ≤5%. The mixture was loaded into a mold and pressed at 20 MPa and 70 ℃ for 40 s to obtain the finished energetic material.
[0029] Example 4; The difference between Example 4 and Example 2 is that citric acid in step (2) is replaced with maleic anhydride, and the other steps are the same as in Example 2.
[0030] Example 5; The difference between Example 5 and Example 2 is that poplar wood powder in step (2) is replaced with bamboo powder, and the other steps are the same as in Example 2.
[0031] Example 6; The difference between Example 6 and Example 2 is that poplar wood powder in step (2) is replaced with corn straw powder, and the other steps are the same as in Example 2.
[0032] Comparative Example 1; The difference between Comparative Example 1 and Example 2 is that step (2) is omitted, and step (3) is changed to: 85 parts by weight of poplar wood powder, 6 parts of polyvinyl alcohol, 3 parts of nano cerium dioxide and 3.5 parts of zinc stearate are mixed, deionized water is added to adjust the moisture content to 18%, and the mixture is extruded and granulated using a twin-screw extruder at 85°C and a screw speed of 120 r / min, and then cut into fuel phase particles with a particle size of 2 mm; the remaining steps are the same as in Example 2.
[0033] Comparative Example 2; The difference between Comparative Example 2 and Example 2 is that step (1) is omitted, and step (4) is changed to: two-phase mixing and molding: by weight, 25 parts of fuel phase particles and 75 parts of potassium chlorate raw powder are added to a three-dimensional mixer and mixed at 35 r / min for 18 min, with a mixing uniformity variation coefficient ≤ 5%; the mixture is loaded into a mold and pressed at 18 MPa and 65°C for 30 s to obtain the finished energetic material; the remaining steps are the same as in Example 2.
[0034] Comparative Example 3; The difference between Comparative Example 3 and Example 2 is the difference in step (3). Step (3) is changed to: 85 parts by weight of modified wood powder and 6 parts by weight of polyvinyl alcohol are mixed, deionized water is added to adjust the moisture content to 18%, and the mixture is extruded and granulated at 85°C and 120 r / min using a twin-screw extruder, and then cut into fuel phase particles with a particle size of 2 mm; the remaining steps are the same as in Example 2.
[0035] Test and Results Analysis Combustion rate test: The energetic materials of Example 1 and each comparative example were made into standard propellant charges with a diameter of 10 mm and a length of 50 mm. These were then horizontally burned, and the linear combustion rate was measured in mm / s. The test results are shown below. Figure 1 .
[0036] Depend on Figure 1 It can be seen that the combustion rate of Example 1 was 4.5 mm / s, the highest among the four groups of samples; the combustion rates of Comparative Examples 1, 2, and 3 were 2.2 mm / s, 3.6 mm / s, and 2.8 mm / s, respectively. This indicates that citric acid modification can optimize the interfacial activity of biomass, and the combination of nano-cerium dioxide and zinc stearate can catalyze the combustion reaction. The synergistic effect of these two components and the microencapsulation process makes the combustion rate of Example 1 significantly better than that of the comparative examples.
[0037] Storage stability test: After being placed in an environment of 25℃ and 75% relative humidity for 12 months, the performance degradation rate was measured, and the unit is %. The test results are shown below. Figure 2 .
[0038] Depend on Figure 2 It can be seen that the performance degradation rate of all four groups of samples increased with the extension of storage time, but the differences were significant: the degradation curves of Comparative Example 1 and Comparative Example 2 increased steeply, with degradation rates of 4.9% and 4.6% respectively after 12 months; the degradation curve of Comparative Example 3 was relatively gentle, with a degradation rate of 1.7% after 12 months; the degradation curve of Example 1 was the gentlest throughout, with a degradation rate of only 1.5% after 12 months. This indicates that the microcapsule coating of sodium lignosulfonate can form a dense water-proof barrier on the surface of potassium chlorate, effectively inhibiting the deliquescence failure of oxidants. Combined with the synergistic effect of biomass modification and functional additives, Example 1 exhibited the best storage stability.
[0039] Impact sensitivity test: The energetic materials prepared in Examples 1-6 and Comparative Examples 1-3 were tested according to GJB772A-97 "Test Methods for Explosives". The drop weight was 10 kg and the drop height was 25 cm. The explosion probability was determined and the unit was .
[0040] Combustion heat test: The energetic materials prepared in Examples 1-6 and Comparative Examples 1-3 were tested according to GB / T213-2008 "Determination of calorific value of coal" using the oxygen bomb calorimetry method, with units of kJ / g.
[0041] Moisture absorption rate test: The energetic materials prepared in Examples 1-6 and Comparative Examples 1-3 were placed in an environment of 25°C and 75% relative humidity for 12 months, and the mass gain rate was measured, in units of %.
[0042] Carbon monoxide content test: The carbon monoxide content in the gas after combustion of the energetic materials prepared in Examples 1-6 and Comparative Examples 1-3 was determined by infrared spectroscopy. The unit is mg / g. The test results are shown in Table 1.
[0043] Table 1
[0044] As shown in Table 1, the performance indicators of Examples 1-6 are significantly better than those of Comparative Examples 1-3, and all meet the requirements of impact sensitivity ≤10%, heat of combustion ≥4.5kJ / g, moisture absorption rate ≤1.5% over 12 months, and carbon monoxide content ≤3.0mg / g.
[0045] In Example 4, citric acid was replaced with maleic anhydride. In Examples 5 and 6, poplar wood powder was replaced with bamboo powder and corn stalk powder, respectively. The prepared energetic materials all exhibited good performance indicators. This demonstrates that the technical solution of the present invention has good versatility for different biomass substrates and different modifiers, and is suitable for the resource utilization of various agricultural and forestry wastes.
[0046] Comparative Example 1, which did not use citric acid to chemically modify the biomass substrate, exhibited an impact sensitivity as high as 33.2%, significantly higher than the 7.0-7.7% of Examples 1-6; its heat of combustion was only 4.3 kJ / g, significantly lower than the examples; and its moisture absorption rate was 7.8%, both higher than the examples. This indicates that modifying the biomass substrate with citric acid can gently modify the hydroxyl groups on the biomass surface, reduce active sites, thereby lowering the material's mechanical sensitivity, while retaining the high heat of combustion of cellulose and improving its hydrophobic properties.
[0047] Comparative Example 2, which did not use sodium lignosulfonate microcapsule coating for potassium chlorate, had a 12-month moisture absorption rate of 7.5%, while Example 2 had a moisture absorption rate of only 0.9%. This indicates that the sodium lignosulfonate shell can form a dense physical isolation structure on the surface of potassium chlorate particles, effectively preventing the intrusion of external moisture, inhibiting the deliquescence and decomposition of potassium chlorate, and thus improving the storage stability of the material.
[0048] Comparative Example 3, without the added functional additives of nano-cerium dioxide and zinc stearate, had a carbon monoxide content as high as 4.2 mg / g. This indicates that nano-cerium dioxide can provide catalytically active sites, promote electron transfer between the fuel and oxidant phases, and accelerate combustion reaction kinetics; while zinc stearate forms a lubricating protective layer on the particle surface, reducing the probability of frictional heat generation. The combined use of these two components produces a synergistic effect, significantly reducing toxic gas emissions while increasing the combustion rate.
[0049] This invention utilizes citric acid or maleic anhydride to chemically modify the biomass substrate, reducing the number of polar hydroxyl groups on the biomass surface through esterification, thereby improving its interfacial compatibility with potassium chlorate while retaining the natural high heat of combustion of cellulose. Secondly, potassium chlorate is microencapsulated with sodium lignosulfonate to form a dense core-shell isolation structure, preventing the intrusion of environmental moisture and buffering mechanical stimulation. Furthermore, a functional additive combining nano-cerium dioxide and zinc stearate is introduced into the fuel phase, providing synergistic effects of catalytic combustion and lubrication / moisture protection. These three elements work together to enable the energetic material to achieve rapid and complete combustion release under conditions of low sensitivity and high storage stability.
[0050] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. A biomass and potassium chlorate solid-state two-phase energetic material, characterized in that, The energetic material is obtained by compounding a fuel phase and an oxidant phase; The fuel phase comprises a biomass substrate, a modifier, a binder, and functional additives. The biomass substrate is chemically modified by the modifier and then mixed with the binder and the functional additives to form fuel phase particles. The oxidant phase is potassium chlorate microcapsules with a core-shell structure formed by encapsulation with sodium lignosulfonate. The functional additive is composed of nano-cerium dioxide and zinc stearate.
2. The energetic material according to claim 1, characterized in that, The biomass substrate is selected from at least one of poplar wood powder, bamboo powder, and corn stalk powder.
3. The energetic material according to claim 1, characterized in that, The modifier is selected from at least one of citric acid and maleic anhydride.
4. A method for preparing an energetic material as described in any one of claims 1-3, characterized in that, Includes the following steps: (1) Dissolve sodium lignosulfonate in deionized water to prepare a coating solution, add potassium chlorate powder and stir evenly to prepare a suspension, spray dry, collect and sieve to obtain potassium chlorate microcapsules coated with sodium lignosulfonate. (2) After drying the biomass substrate, mix it with the modifier, add deionized water and stir to react. After the reaction is completed, filter and dry to obtain the modified biomass substrate. (3) The modified biomass substrate is mixed with binder, nano-cerium dioxide and zinc stearate, and deionized water is added to adjust the moisture content before extrusion granulation to obtain fuel phase particles; (4) The fuel phase particles and the potassium chlorate microcapsules are mixed evenly and then pressed into shape to obtain an energetic material.
5. The method according to claim 4, characterized in that, The fuel phase particles described in step (3) include, by weight, 80-90 parts of modified biomass substrate, 5-7 parts of binder, 2-4 parts of nano-cerium dioxide and 1.5-4.5 parts of zinc stearate.
6. The method according to claim 4, characterized in that, The modified biomass substrate mentioned in step (2) comprises, by weight, 75-88 parts of dried biomass substrate and 4-8 parts of modifier.
7. The method according to claim 4, characterized in that, The parameters for spray drying in step (1) are: inlet air temperature of 180~200℃, outlet air temperature of 80~90℃, and feed rate of 5~10mL / min.
8. The method according to claim 4, characterized in that, In step (4), the fuel phase particles account for 20-28% of the total mass of the energetic material, and the potassium chlorate microcapsules account for 72-80% of the total mass of the energetic material.
9. The method according to claim 4, characterized in that, The pressing pressure in step (4) is 15~20MPa, the pressing temperature is 60~70℃, and the pressing time is 20~40s.